Service-quality scale for Chinese working mothers’ e-learning platforms: development and validation - Zhang, Man; Md Hashim, Azhari; Wan Omar, Wan Noor Faaizah; Zhang, Xin; Zhong, Jing (2025)
The rapid progression of online education has rendered the enhancement of service quality a key concern in augmenting user experience. This study aims to create service quality rating scales for online education platforms specifically designed for Chinese working mothers, in order to comprehensively assess the unique needs and experiences of this demographic while using the platforms. The scale was created based on the SERVQUAL framework, and the initial dimensions were established through a literature review. The conventional dimensions of service quality were refined and redefined from the user experience viewpoint, highlighting essential factors such as interaction experience, emotional support, interface intuitiveness, and personalized service, to more precisely reflect the service quality perceived by working mothers in China. The study utilized a questionnaire for data collection, employing SPSS 26.0 and AMOS 24.0 to conduct exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to evaluate the structural validity and reliability of the scales, respectively. The finalized measure had six dimensions: responsiveness, reliability, assurance, tangibility, empathy, and work-family balance, including a total of 40 items. The empirical results reveal that the established scale exhibits robust reliability and validity, providing innovative perspectives on the application of service quality theory from the user experience viewpoint while also delivering targeted recommendations for improving service design in online education platforms.